Infrared Thermography as Non-invasive Tool for Early Detection of Lameness in Dairy Cows - Ilievska Ksenija , Atanasov Branko , Pendovsk Lazo, Musliu Hajrulai Zehra , Trojachanec Plamen (My University, 2020)
Lameness represents a serious problem in dairy cattle industry, that results with major economic losses due to infertility, weight loss, reduced milk yield and premature culling. Laminitis, digital dermatitis characterised by erosive infection on the heels, digits or coronary band, sole ulcer and white linie disease are most common cause for impaired locomotion and mobility in dairy cows. Due to the elevated metabolic activity or inflammatory process, the temperature of the coronary band and the surrounding skin usually increases. Since most of the diagnostic methods, requires the animal to stand still, which is not always possible, an infrared thermography (IR) as non-invasive diagnostic technique is used to detect emitted infrared radiation and convert into the electrical impulses, that can be visualized in different colours on a screen. The objective of this study was to examine the potential of IR thermography for early detection of different hoof pathologies in dairy cows. Non-contact infrared thermography was performed using the hand-held portable thermal camera (Testo 880-3 Thermal imager, Testo AG, Germany) on the hind claws of total 69 lame and non-lame lactating Holstein-Friesian cows in a tie-stall system. The emissivity value was set at 0.95 with a precision of ±0.01°C. Hoof temperature was measured at approximately equal distance of 1 m from the dorsal and plantar surface of the hoofs. Ambient temperature was recorded all the time, during the study. The temperature difference (ΔT) on the coronary band and the plantar side of the hoof were recorded, by determining the highest and lowest temperature an the given region. Hight significant difference (p<0,01) were detected in animals with Digital dermatitis (DD) comparing to the animals with Laminitis (Lam), Interdigital dermatitis (IDD) and animals with healthy hoofs (H). Infrared thermography is a promising diagnostic tool for early detection of lameness in dairy cows, but further research are needed for validation of this method in field conditions.
Keywords: lameness, infrared thermography, dairy cows